Scanning‐Tunneling‐Spectroscopy‐Directed Design of Tailored Deep‐Blue Emitters1. Issue 3 (17th December 2014) - Sanning, Jan; Ewen, Pascal R.; Stegemann, Linda; Schmidt, Judith; Daniliuc, Constantin G.; Koch, Tobias; Doltsinis, Nikos L.; Wegner, Daniel; Strassert, Cristian A.
Abstract Frontier molecular orbitals can be visualized and selectively set to achieve blue phosphorescent metal complexes. For this purpose, the HOMOs and LUMOs of tridentate PtII complexes were measured using scanning tunneling microscopy and spectroscopy. The introduction of electron‐accepting or ‐donating moieties enables independent tuning of the frontier orbital energies, and the measured HOMO–LUMO gaps are reproduced by DFT calculations. The energy gaps correlate with the measured and the calculated energies of the emissive triplet states and the experimental luminescence wavelengths. This synergetic interplay between synthesis, microscopy, and spectroscopy enabled the design and realization of a deep‐blue triplet emitter. Finding and tuning the electronic "set screws" at molecular level constitutes a useful experimental method towards an in‐depth understanding and rational design of optoelectronic materials with tailored excited state energies and defined frontier‐orbital properties.